Impact of milk supply schemes on rural economy in milk collection areas of Madhavaram milk supply scheme, Chingleput - Tamil Nadu : bench-mark survey - Singh, H. P. (Indian Agricultural Statistics Research Institute, 1978)
Survey done during 1975-1976.